Diseño de un sistema de tratamiento de aguas residuales para el barrio Guaguayme Alto del cantón Zamora - Zapata Jara, Anderson Fabián (2023)
The following work presents the design of a vertical subsurface flow artificial wetland, according to the conditions of the Guaguayme Alto neighborhood in the Zamora canton. This sector is a small urban center that discharges its wastewater directly into the creek. The choice of the artificial wetland is justified because in recent years this technology has been mainly applied in rural sectors due to its low installation and operation costs and obtaining good results. Based on this, the main objective and in accordance with the study area conditions, the design of this treatment was carried out. To do this, wastewater samples were collected on four different days to determine the degree of contamination, and several systems applied mainly in small towns were evaluated for treatment selection. Finally, the design of the selected treatment was carried out, together with the evaluation of the impact that its implementation can generate. In the design of wastewater treatment plants for small communities, it is important to consider the state of the wastewater and choose the appropriate treatment systems, especially in rural areas due to the economic limitations that these places may present.